Assessment of the static and fatigue strength of a precession driven dynamo under thermomechanical loads. Issue 1 (December 2014) - Beisitzer, Stephan; Scheffler, Michael; Beitelschmidt, Michael
Abstract At the Helmholtz‐Zentrum Dresden‐Rossendorf an experimental plant is developed to investigate the formation of magnetic fields in flows of liquid metals. Because of the enormous hazard potential of the used liquid sodium it is essential to avoid any damages during operation and so a detailed analysis using the finite element method is necessary considering the various mechanical and thermal loads. Therefore several tens of thousands load cases have to be taken into account. Hence an algorithm is developed to identify the relevant stresses referring to FKM guideline which are used for the static and fatigue strength assessment. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)